Reply to Comment on ‘Self-thinning forest understoreys reduce wildfire risk, even in a warming climate’ - Zylstra, Philip; Lindenmayer, David B; Bradshaw, S Don (Institute of Physics (IoP), 2024)
Our previous analysis of mapped records of forest fires in National Parks in Southwestern Australia showed that fires initiated a pulse in flammability (the likelihood of a point being burned by wildfire), but that flammability declined as forests matured (Zylstra et al 2022 Environ. Res. Lett.17 044022). This reduction in flammability was contrary to that expected from modelling used by the West Australian Government to guide management, but consistent with expectations from peer-reviewed fire behaviour science and published ecological drivers of fire behaviour. Miller et al (2024 Environ. Res. Lett.) argued that our reported decline in flammability of long-unburnt forest is an artefact of poor data quality including flawed records kept by the West Australian Government, along with fewer and smaller sample sizes in long-unburnt forest. These problems, they claim, biased these age-classes toward values of zero flammability due to a rounding error. Critically, Miller et al (2024 Environ. Res. Lett.) did not test their hypothesis by repeating the analysis with these data removed. Here, we show that Miller et al's (2024 Environ. Res. Lett.) concerns are dependent upon the mathematical fallacy that rounding errors only occur in one direction (rounding flammability down to zero), when they have an equal likelihood of rounding upward and elevating flammability. The effect of this is to introduce noise rather than bias. We tested their hypothesis by repeating the analysis of Zylstra et al (2022 Environ. Res. Lett.17 044022) with a better suited statistical method on an improved and expanded dataset after removing the small patches that Miller et al (2024 Environ. Res. Lett.) proposed would bias the findings. Contrary to the objections of Miller et al (2024 Environ. Res.Lett.), removing lower quality data revealed that the mature forests were even less flammable than expected, so that only annual prescribed burning could reduce bushfire likelihood below that in forests unburnt for 56 years or more. Our findings highlight the role of prescribed burning in creating a more flammable landscape.